Passenger transport in rural and sparsely populated areas in France - Christophe Saroli (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2015)
Improving mobility is a major issue in sparsely populated areas. The low population density in these localities often means that longer journeys are required to access services, carry out everyday activities or maintain social links. Whole sections of the population - in particular older people, young people, stay-at-home parents in single-car households, and seasonal workers - are effectively handicapped in mobility terms by inadequate public transport provision and an overdependence on people who have cars.
Keywords: 330; Öffentlicher Verkehr; Ländlicher Raum; Bevölkerungsdichte; Verkehrsplanung; Nachhaltige Entwicklung; Frankreich